Contribution of Second and Higher‐Order Births to Adolescent Fertility in Mexico. Issue 1 (31st January 2019) - Sánchez‐Pájaro, Andrés; Braverman‐Bronstein, Ariela; De Castro, Filipa; Vidaña‐Pérez, Dèsirée; Villalobos‐Hernández, Aremis; Barrientos‐Gutiérrez, Tonatiuh
Abstract: This study estimates the contribution of second and higher‐order births to the adolescent fertility rate in Mexico from 2006 to 2014. We used data from nationally representative surveys for 2006, 2009, and 2014 to estimate the adolescent fertility rate, and the first, second, and higher‐order birth components for the triennium prior to each survey at the national and state level. Our results showed that the second and higher‐order component was 16.3 births per 1, 000 women in 2003–05, 14.9 in 2006–08, and 16.9 in 2011–13. Second and higher‐order births represented 25.9 percent of all teen births in 2003–05, 21.6 percent in 2006–08, and 21.9 percent in 2011–13. Second and higher‐order births were heterogeneous across states. We found that second and higher‐order births are highly prevalent and important contributors to the adolescent fertility rate. Postponing second and higher‐order births would benefit both mothers and children. Monitoring them provides crucial information on the demand of targeted health system strategies that address the reproductive health needs of adolescent mothers. Interventions to prevent second and higher‐order pregnancies must be developed and implemented.